"Somos ecuatorianos, somos infelices, somos indios i pleno derecho tenemos de la protección": prácticas populares de propiedad y justicia en la provincia de Loja entre 1925-1945 (Estudios) - González Alulima, Ángel Francisco (2022)
The article studies how the indigenous population of Loja designed and applied a series of legal tools to redefine the land property regime. This was possible because the Juliana revolution allowed the revitalization of legal resources from a radical tradition of law. This allowed defining a recognized pluralism within the Ecuadorian legal order, with a special role of the popular sectors, which was vindicated during la Gloriosa of 1944.